Comparison of fire resistance of damaged fireproofed steel beams under hydrocarbon pool fire and ASTM E119 fire exposure. (10th June 2019) - Mahamid, Mustafa; Taghipour Anvari, Ataollah; Torra-Bilal, Ines; Brindley, Tom; McNallan, Michael
Abstract : Purpose: The purpose of this paper is to investigate different types of fire on structural steel members with damaged fireproofing. Two types of fire scenarios are considered, ASTM E119 fire and Hydrocarbon fire. In industrial facilities such as oil refineries, certain units maybe subjected to hydrocarbon fire, and its effect might be different than standard fire. The purpose of this study is to compare both types of fire scenarios on steel beams with damaged fireproofing and determine the fire rating of the damaged beams under each fire scenario. Design/methodology/approach: The study is performed using computational methods, thermal-stress finite element analysis that is validated with experimental results. The results of practical beam sizes and typical applied loads in such structures have been plotted and compared with steel beams with non-damaged fireproofing. Findings: The results show significant difference in the beam fire resistance between the two fire scenarios and show the fire resistance for beam under each case. The study provides percentage reduction in fire resistance under each case for the most commonly used cases in practice under different load conditions. Originality/value: Extensive literature search has been performed by the authors, and few studies were found relevant to the topic. The question this study answers comes up regularly in practice. There are no standards to codes that address this issue.